The response of soil microbial communities to soil erodibility depends on the plant and soil properties in semiarid regions. (16th June 2021) - Zhang, Min; Dong, Liguo; Wang, Ying; Bai, Xiaoxiong; Ma, Zitong; Yu, Xuan; Zhao, Zhong
Abstract: Natural succession and afforestation are the two main restoration methods of degraded soil in semiarid and arid regions. Up to now, the soil microbial communities and their roles in soil erodibility have been unclear. Our work aimed to evaluate the effects of ecological restoration on the diversity and composition of soil microbial communities at depths of 0–20 cm and their interaction with soil erodibility. Four main restoration types, natural succession land and Pinus tabuliformis, Armeniaca sibirica, and Robinia pseudoacacia plantations were chosen. Restoration with different vegetation communities decreased the soil erodibility K ‐factor ( K ) by 13.37–20.64%. Proteobacteria, Acidobacteria, and Actinobacteria were dominant bacterial phyla at all sites. The dominant fungal phyla were Basidiomycota, Ascomycota, and Zygomycota. However, there were obvious differences in bacterial and fungal communities among restoration types due to variations in plant and soil properties. Redundancy analysis showed that the soil microbial communities explained 67.30% of the total variance in soil erodibility. Bacterial communities mainly affect the microaggregate formation, whereas fungal communities have a greater effect on macroaggregate formation. Additionally, the structural equation modeling also suggests that vegetation characteristics, soil organic carbon, and fungal communities, and macroaggregates (> 5 mm) have positive effects on mean weight diameter. Therefore, the combination of vegetation community, soil properties, and microbial communities improves the soil structure against erosion in this area.